Risk Factors for Mortality Among Children Younger Than Age 5 Years With Severe Diarrhea in Low- and Middle-income Countries: Findings From the World Health Organization-coordinated Global Rotavirus and Pediatric Diarrhea Surveillance Networks. (7th July 2022) - Hartman, Rachel M; Cohen, Adam L; Antoni, Sebastien; Mwenda, Jason; Weldegebriel, Goitom; Biey, Joseph; Shaba, Keith; de Oliveira, Lucia; Rey, Gloria; Ortiz, Claudia; Tereza, Maria; Fahmy, Kamal; et al.
Abstract: Background: Diarrhea is the second leading cause of death in children younger than 5 years of age globally. The burden of diarrheal mortality is concentrated in low-resource settings. Little is known about the risk factors for childhood death from diarrheal disease in low- and middle-income countries. Methods: Data from the World Health Organization (WHO)-coordinated Global Rotavirus and Pediatric Diarrhea Surveillance Networks, which are composed of active, sentinel, hospital-based surveillance sites, were analyzed to assess mortality in children <5 years of age who were hospitalized with diarrhea between 2008 and 2018. Case fatality risks were calculated, and multivariable logistic regression was performed to identify risk factors for mortality. Results: This analysis comprises 234 781 cases, including 1219 deaths, across 57 countries. The overall case fatality risk was found to be 0.5%. Risk factors for death in the multivariable analysis included younger age (for <6 months compared with older ages, odds ratio [OR] = 3.54; 95% confidence interval [CI], 2.81–4.50), female sex (OR = 1.18; 95% CI, 1.06–1.81), presenting with persistent diarrhea (OR = 1.91; 95% CI, 1.01–3.25), no vomiting (OR = 1.13; 95% CI, .98–1.30), severe dehydration (OR = 3.79; 95% CI, 3.01–4.83), and being negative for rotavirus on an enzyme-linked immunosorbent assay test (OR = 2.29; 95% CI, 1.92–2.74). Cases from the African Region had the highest odds of death compared with other WHO regions (OR = 130.62 comparing the African Region with the European Region; 95% CI, 55.72–422.73), whereas cases from the European Region had the lowest odds of death. Conclusions: Our findings support known risk factors for childhood diarrheal mortality and highlight the need for interventions to address dehydration and rotavirus-negative diarrheal infections.